Trunk motion control during the flight phase while hopping considering angular momentum of a humanoid. (17th November 2018) - Otani, Takuya; Hashimoto, Kenji; Isomichi, Takaya; Natsuhara, Akira; Sakaguchi, Masanori; Kawakami, Yasuo; Lim, Hun-ok; Takanishi, Atsuo
ABSTRACT: In previous studies, various stabilizing control methods for humanoids during the stance phase while hopping and running were proposed. Although these methods contribute to stability while hopping and running, it is possibility that the control during the flight phase could also affect the stability. In this study, we investigated whether the control during the flight phase can affect the stability of a humanoid while running. To achieve stable hopping, we developed a control system that accounts for the angular momentum of the whole body during the flight phase. In this system, the angular momentum generated by the motion of the lower body in each time interval is calculated during the flight phase, and the trunk joints are controlled to generate the angular momentum necessary to compensate for the deviation of the waist posture, which is used as the reference point for the motion coordinate system of the robot. Once the proposed control system was developed and simulated, we found that the hopping duration in the unconstrained state was extended. GRAPHICAL ABSTRACT: